Conimbricenses.Org: an open-access online repository on the Philosophical tradition in Coimbra - Simone Guidi (DEDiCA, 2018)
Only a few Institutions in Europe can praise to be such an important chapter of the European culture like the University of Coimbra, and its unique philosophical tradition, already started in the Middle Ages, is still nowadays a crucial passage to understand the entire History of Philosophy. The Conimbricenses.org project aims to contribute to demonstrating that. Launched online in 2018 by the University of Coimbra’s Instituto de Estudos Filosóficos (IEF), under the direction of Prof. Mário Santiago de Carvalho and the coordination of Dr. Simone Guidi, it will give access from worldwide to a large collection of information, accurate entries, updated bibliographies, and direct links to the digital version of the most important documents related to Coimbra.